The effect of daily heart rate workloads on preseason, midseason, and postseason oxygen consumption in Division I basketball - Howard, M.; Sanders, G. J.; Kollock, R. O.; Peacock, C. A.; Freire, R. (The Journal of Strength and Conditioning Research, 2024)
Basketball is a dynamic sport, requiring athletes to elicit a high-level of physical, tactical, technical, and psychological attributes and athletes must possess a robustly trained aerobic energy system. There is no research to assess how objectively measured training loads throughout a season influence aerobic capacity. The following study was a retrospective analysis of an NCAA Division I women`s basketball team throughout a 5-month (23-week) competitive season. Data were sorted into season half totals and maximal oxygen consumption was recorded before, at the midway point and within 1-week postseason. Twelve athletes were monitored during each practice, pregame shoot around, scrimmage, and game for a total of 1,378 recorded sessions with a valid heart rate-based wearable microsensor (Polar Team Pro) during the season. There was a main effect of time for VO2max throughout the season (p < 0.001). Post hoc analysis revealed there was a significant increase in VO2max from preseason to postseason (p < 0.001). Interestingly, there were significant (p = 0.001 for all) decreases from the first half to the second half of the season for training load, and time allocated to HRZone1-4, but no difference in time for the most intense zone, HRzone5. Conclusion: Oxygen consumption significantly increased 7.5% from preseason to postseason despite a reduction in overall work. The only training intensity that was not different from the first half to second half of the season was time in the highest heart rate intensity zone =85% of HRmax.